2010
DOI: 10.1523/jneurosci.2825-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of Top-Down Frontal Cognitive Control Networks Underlying the Development of Inhibitory Control: A Functional Magnetic Resonance Imaging Effective Connectivity Study

Abstract: The ability to voluntarily inhibit responses to task-irrelevant stimuli, which is a fundamental component of cognitive control, has a protracted development through adolescence. Previous human developmental imaging studies have found immaturities in localized brain activity in children and adolescents. However, little is known about how these regions integrate with age to form the distributed networks known to support cognitive control. In the present study, we used Granger causality analysis to characterize d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
195
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(208 citation statements)
references
References 88 publications
13
195
0
Order By: Relevance
“…Existing literature suggests that the lateral PFC is a source of top-down biasing signal that influences sensorimotor processes (Hwang et al, 2010;Johnston and Everling, 2011). We found that in response to the heightened control demand in AS trials, beta-band power increased in the right DLPFC during the preparatory period, and causally influenced FEF alphaband activity.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature suggests that the lateral PFC is a source of top-down biasing signal that influences sensorimotor processes (Hwang et al, 2010;Johnston and Everling, 2011). We found that in response to the heightened control demand in AS trials, beta-band power increased in the right DLPFC during the preparatory period, and causally influenced FEF alphaband activity.…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that these methods make the same set of assumptions (e.g., stationarity) about the time series. Accumulating evidence demonstrates the effectiveness of using Granger causality to characterize fMRI data (Rypma et Hwang et al, 2010;Jiao et al, 2011). Moreover, recent work shows that both resting-state and task-state fMRI data are well described by autoregressive models, which are the basis for deriving Granger causality (Sridharan et al, 2007;Bressler and Seth, 2011;Hamilton et al, 2011).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Age-related differences in top-down control are associated with a strengthening of effective connectivity between frontal and posterior brain regions (Hwang et al, 2010). Recent results from resting state functional connectivity MRI (fcMRI) describe changes in functional networks during development as an increase in segregation (thus a decrease in short-range connections) and an increase in integration (largescale connections; Fair et al, 2009Fair et al, , 2007.…”
Section: Maturational Changes In the Structures Functions And Mechamentioning
confidence: 99%
“…Measures of functional connectivity may offer a useful tool for elucidating the relevance of age-graded changes in the interaction of the two components for WM performance. Initial studies of this kind point to profound developmental differences in the configuration and recruitment of brain networks in childhood (e.g., Hwang et al, 2010;Jolles et al, 2011) and adulthood (e.g., Andrews-Hanna et al, 2007;Damoiseaux et al, 2008). Developmental changes in childhood seem to reflect a decrease in short-range connections and an increase in large-scale connections (e.g., Fair et al, 2009Fair et al, , 2007.…”
Section: Questions For Future Researchmentioning
confidence: 99%